A subset of SR proteins activates splicing of the cardiac troponin T alternative exon by direct interactions with an exonic enhancer. - Ramchatesingh, J (1995)
The cardiac troponin T pre-mRNA contains an exonic splicing enhancer that is required for inclusion of the alternative exon 5. Here we show that enhancer activity is exquisitely sensitive to changes in the sequence of a 9-nucleotide motif (GAGGAAGAA) even when its purine content is preserved. A series of mutations that increased or decreased the level of exon inclusion in vivo were used to correlate enhancer strength with RNA-protein interactions in vitro. Analyses involving UV cross-linking and immunoprecipitation indicated that only four (SRp30a, SRp40, SRp55, and SRp75) of six essential splicing factors known as SR proteins bind to the active enhancer RNA. Moreover, purified SRp40 and SRp55 activate splicing of exon 5 when added to a splicing-deficient S100 extract. Purified SRp30b did not stimulate splicing in S100 extracts, which is consistent with its failure to bind the enhancer RNA. In vitro competition of SR protein splicing activity and UV cross-linking demonstrated that the sequence determinants for SR protein binding were precisely coincident with the sequence determinants of enhancer strength. Thus, a subset of SR proteins interacts directly with the exonic enhancer to promote inclusion of a poorly defined alternative exon. Independent regulation of the levels of SR proteins may, therefore, contribute to the developmental regulation of exon inclusion.